(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
Linguistics is very broad branch of language learning and it always attracts language learners with its peculiar features. The more you learn linguistics the more knowledge which is in reality important to your life you get and as a result of this you show more interest for the linguistics. This work explains why it is crucial to learn linguistics while you are learning a foreign language. And in my opinion it will be really beneficial for readers. There are several questions to answer. Firstly, let’s answer the question "What is linguistics?". Simply put, linguistics is the study of language, how it works, how it is acquired, and how people use it to communicate. Although linguists are often interested in and can speak a variety of languages, linguists know more about how language works, rather than having the ability to speak and understand multiple languages. A polyglot is a person who speaks a multitude of languages.